2007
DOI: 10.1371/journal.pone.0000973
|View full text |Cite
|
Sign up to set email alerts
|

The Genetic Signature of Sex-Biased Migration in Patrilocal Chimpanzees and Humans

Abstract: A large body of theoretical work suggests that analyses of variation at the maternally inherited mitochondrial (mt)DNA and the paternally inherited non-recombining portion of the Y chromosome (NRY) are a potentially powerful way to reveal the differing migratory histories of men and women across human societies. However, the few empirical studies comparing mtDNA and NRY variation and known patterns of sex-biased migration have produced conflicting results. Here we review some methodological reasons for these i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
3
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 24 publications
5
89
3
1
Order By: Relevance
“…Standardized F ST was usually several times higher than unstandardized F ST for microsatellite loci (e.g., Criscione et al 2007;Jordan and Snell 2008;González-Pérez et al 2009). Standardizing of F ST became now a required procedure when different markers are compared or combined for analysis (e.g., Langergraber et al 2007;Ryynänen et al 2007). Therefore, our study as well as other published studies confirmed a necessity of using a standardized measure of genetic differentiation when measures are based on different genetic markers.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Standardized F ST was usually several times higher than unstandardized F ST for microsatellite loci (e.g., Criscione et al 2007;Jordan and Snell 2008;González-Pérez et al 2009). Standardizing of F ST became now a required procedure when different markers are compared or combined for analysis (e.g., Langergraber et al 2007;Ryynänen et al 2007). Therefore, our study as well as other published studies confirmed a necessity of using a standardized measure of genetic differentiation when measures are based on different genetic markers.…”
Section: Discussionsupporting
confidence: 81%
“…They are independent of the amount of genetic variation and therefore suitable for comparisons between studies that employ different genetic markers. Although these measures are relatively new, they were already used in a few recently published studies that, together with our study, validated their use (e.g., Criscione et al 2007;Kettle et al 2007;Langergraber et al 2007;Ryynänen et al 2007;Leinonen et al 2008). Standardized F ST was usually several times higher than unstandardized F ST for microsatellite loci (e.g., Criscione et al 2007;Jordan and Snell 2008;González-Pérez et al 2009).…”
Section: Discussionsupporting
confidence: 69%
“…We sequenced most of the members of each of the nine groups at the first hypervariable region of the maternally inherited mitochondrial (mt)DNA (354 bases; numbers of adolescent and adult individuals sequenced/number of adolescent and adult group members present at time of sampling in brackets): the Bossou group (12/12) of Guinea, the North (8/11) and South (16/26) groups of Taï National Park, Cote d'Ivoire, the Sonso group (28/28) of Budongo Forest Reserve, Uganda, the Ngogo (89/89) and Kanyawara (20/20) groups of Kibale National Park, Uganda, the M (32/32) and K (3/ Unknown) groups of Mahale Mountains National Park, Tanzania and the Kasekela (38/38) group of Gombe Stream National Park, Tanzania. MtDNA sequences for five of the groups were previously published: Bossou [46], Sonso [47,48], Gombe [49], Ngogo [47,48] and Kanyawara [47,48]. We generated new mtDNA sequences for the Taï North and South groups and the Mahale M and K groups, following previously described procedures [47,48].…”
Section: Methodsmentioning
confidence: 99%
“…We analyzed 51 individuals of the M group in Mahale but found only four haplotypes (Table 1). Langergraber et al (2007) analyzed mitochondrial DNA of three chimpanzee communities in Uganda and found 14, 16, and seven haplotypes among 28, 94, and 20 individuals, respectively. Thus, there were fewer haplotypes per social community in southern Tanzania than in Uganda.…”
Section: Genetic Diversitymentioning
confidence: 99%